Single Dose Antibiotic Prophylaxis in Outpatient Oral Surgery Comparative Study - Fadia Y. Alhamdani; Faaiz Y.Alhamdani (College of Pharmacy University of Baghdad, 2017)
It is clear that correct application of antibiotic prophylaxis can reduce the incidence of infection  resulting from the bacterial  inoculation in a variety of clinical situations; it cannot   prevent  all  infections  any  more  than it  can   eliminate  all  established infections. Optimum  antibiotic   prophylaxis  depends on:  rational  selection  of the drug(s),  adequate  concentrations  of the  drug  in  the  tissues that  are at risk, and attention to  timing  of  administration.  Moreover,  the  risk  of  infection  in  some situations  does not outweigh  the risks which  attend the administration of even the safest antibiotic drug. The aim of this study was to compare between 2 prophylactic protocols  in  out  patients  undergoing  oral  surgical  procedures.  Thirty   patients, selected from the attendants of oral surgery clinic in Al-Karamah Dental Center, were subjected to different oral surgical procedures under local  anesthesia. These patients were given single dose antibiotic  prophylaxis in 2 groups; 1st group were 15 patients given 1 million i.u. of procaine  penicillin  I.M. 30 minutes  before oral  surgery, 2nd group were 15 patients given 600mg clindamycin orally 1 hours before oral surgery. The  maximum  time  for  all  procedures  was 2 hours. There  was  no  difference between  procaine  penicillin  (1 million i.u.), and  clindamycin (600mg),  regimens concerning post operative infection in out patientâ€™s oral surgical procedures. Key words: Antibiotic prophylaxis, outpatient oral surgery